O clima da cidade de Uberlândia-MG - Emerson Malvino da Silva; Washington Luis Assunção (Sociedade & Natureza)
The cities presents the largest and more significant transformations that the man causes in the natural landscape act; the climate is one of the aspect that best expressed the relationship between the society economical and social organization of the urban space. For other side the atmosphere phenomena allies to the geological aspects and geomorphologic, act in the genesis of a variety of landscapes that they influence in the type of organizations of the space.